The ice twins - Tremayne, S. K. (New York : Grand Central Publishing, 2015)
Moving to a tiny Scottish island a year after one of their identical twin daughters, Lydia, dies in an accident, Angus and Sarah are shattered when their surviving daughter claims they have mistaken her identity and that she is actually the twin they believed dead.
Keywords: Twins -- Fiction; Grief -- Fiction; Islands -- Scotland -- Fiction; Twins -- Fiction; Bereavement -- Fiction; Islands -- Scotland -- Fiction; Suspense fiction; Suspense fiction; Psychological fiction